Identification, confirmation and quantification of sulfonamides in kidney and meat of food-producing animals by HPLC-PDA - TIRPENOU A. Ε.; TSIGOURI (Α. Δ. ΤΣΙΓΟΥΡΗ) A. D.; GOUTA (E.H. ΓΟΥΤΑ) E. H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Residue monitoring in animal husbandry and in food of animal origin is based on the implementation of a Surveillance Scheme, according to the legislation (Directive 86/469/EEC1, N. D. 497/89% Regulation (EEC) 2377/903, Directive 96/23/EU4). Among our obligations as a European Union National Reference Laboratory (EU-NRL), we have to develope screening and confirmatory methods. Towards the development and validation of these confirmatory techniques, als for the group of antimicrobials, a method has been developed for sulfa drug determination. These substances are used extensively in livestock for therapeutic as well as for growth promotin purposes. Diserens et al., 19915 method with our modifications, is used in our laboratory to confirm the Four Plate Test6 suspect kidney and meat samples sent from the Regional Field Laboratories (RFLs) of the Ministry of Agriculture. The method’s steps are: extraction, concentration and quantitative elution of sulfa drugs using Solid Phase Extraction (SPE) and their identification, confirmation and quantitation by HPLC/UV with a Photo Diode Array detector. The column used was Hypersil ODS, 5 μιη (250 x 4.6 mm) and the mobile phase was 0.01 M ammonium acetate buffer pH 4.6/MeOH at a gradient mode. The wavelength was monitored at 266 nm, the flow rate of the mobile phase was l.lmL.min ’ and the injection volume was 20 μL. 12 sulfonamides can be simultaneously detected in one run at concentrations as low as 20 μg/kg. The recovery ranges from 60 to 88% for spiked samples at the Maximum Residue Limit of 100 μg/kg.